Laboratory Studies on the Host Preference of Cotton Mealybug ‘Phenacoccussolenopsis’ Tinsely (Hemiptera: Pseudococcidae) in Khartoum State, Sudan - Nawal, Ahmed Mohamed; Awad, KhalafAlla Taha; Abubaker, Haroun Mohamed Adam (Journal of Agronomy Research, 2019)
Cotton mealybug (Phenacoccussolenopsis) is a serious devastating pest which goes on a wide array of plant families. The pest spread all over the world from cool to dry hot regions. The main objective of this study was to investigate the food preference and behavior of P. solenopsis Tinseley (Hemiptera:Pseudococcidae) towards selected host plants in Khartoum State, Sudan, where a multi-choice experiment under laboratory conditions was adopted. Eight plant species were screened for attractiveness and food preference to Cotton mealybug. Where the proportions of the 1st, 2nd and 3rd nymphal instars and the adult females were recorded at 2, 8 and 24 hours after release, and compared with Chinese rose (Rosa chinensis) the control. The result revealed that the proportions of the 1st, 2nd and 3rd nymphal instars and adult females were maximum on plants of family Malvaceae, particularly the Okra (Hibiscus esculentus) followed by Cotton (Gossypium sp.) and Hambouk (Abutilon pannosum) as compared with the control. However, in contrast, the proportions were very low on unpalatable plants like Zaleya (Locally known as Raba) (Zaleyapentandra) and Eggplant (Solanum melongenaL.). However, in contrast, the proportions were very low on unpalatable plants like Zaleya (Locally known as Raba) (Zaleya pentandra) and Eggplant (SolanummelongenaL.). In conclusion, the most favorable host plants of the Cotton mealybug belonging to the family Malvaceae, while the families of Solanaceae [Egg plant (SolanummelongenaL.)] and Aizoaceae (Raba) were found to be the least preferred host plants.
Keywords: Gossypium; Chinese rose; nymphal; instar; Preference